Stem cell-derived cardiomyocytes expressing a dominant negative pacemaker HCN4 channel do not reduce the risk of graft-related arrhythmias - Wulkan, Fanny; Romagnuolo, Rocco; Qiang, Beiping; Valdman Sadikov, Tamilla; Kim, Kyung-Phil; Quesnel, Elya; Jiang, Wenlei; Andharia, Naaz; Weyers, Jill J.; Ghugre, Nilesh R.; Ozcan, Bilgehan; Alibhai, Faisal J.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background Human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) show tremendous promise for cardiac regeneration following myocardial infarction (MI), but their transplantation gives rise to transient ventricular tachycardia (VT) in large-animal MI models, representing a major hurdle to translation. Our group previously reported that these arrhythmias arise from a focal mechanism whereby graft tissue functions as an ectopic pacemaker; therefore, we hypothesized that hPSC-CMs engineered with a dominant negative form of the pacemaker ion channel HCN4 (dnHCN4) would exhibit reduced automaticity and arrhythmogenic risk following transplantation. Methods We used CRISPR/Cas9-mediated gene-editing to create transgenic dnHCN4 hPSC-CMs, and their electrophysiological behavior was evaluated in vitro by patch-clamp recordings and optical mapping. Next, we transplanted WT and homozygous dnHCN4 hPSC-CMs in a pig MI model and compared post-transplantation outcomes including the incidence of spontaneous arrhythmias and graft structure by immunohistochemistry. Results In vitro dnHCN4 hPSC-CMs exhibited significantly reduced automaticity and pacemaker funny current (If) density relative to wildtype (WT) cardiomyocytes. Following transplantation with either dnHCN4 or WT hPSC-CMs, all recipient hearts showed transmural infarct scar that was partially remuscularized by scattered islands of human myocardium. However, in contrast to our hypothesis, both dnHCN4 and WT hPSC-CM recipients exhibited frequent episodes of ventricular tachycardia (VT). Conclusions While genetic silencing of the pacemaker ion channel HCN4 suppresses the automaticity of hPSC-CMs in vitro, this intervention is insufficient to reduce VT risk post-transplantation in the pig MI model, implying more complex mechanism(s) are operational in vivo.